Contributions of UDP-Glucuronosyltransferases to Human Hepatic and Intestinal Metabolism of Ticagrelor and Inhibition of UGTs and Cytochrome P450 Enzymes by Ticagrelor and its Glucuronidated Metabolite - Liu, Shuaibing; Hou, Lei; Li, Cai; Zhao, Yibo; Yao, Xia; Zhang, Xiaojian; Tian, Xin (Frontiers in Pharmacology, 2021)
Ticagrelor is the first reversibly binding, direct-acting, oral P2Y12 receptor inhibitor. The contribution of UDP-glucuronosyltransferases (UGTs) enzymes to the metabolism of ticagrelor to its glucuronide conjugation, ticagrelor-O-glucuronide, in human liver microsomes (HLM) and human intestinal microsomes (HIM), was well characterized in the current study. The inhibition potential of human major UGTs by ticagrelor and ticagrelor-O-glucuronide was explored. The inhibitory effects of ticagrelor-O-glucuronide on cytochrome P450s (CYPs) enzymes were investigated as well. Ticagrelor glucuronidation exhibits substrate inhibition kinetics in both HLM and HIM with apparent Km values of 5.65 and 2.52 μM, Vmax values of 8.03 and 0.90 pmol·min-1·mg protein-1, Ksi values of 1343.0 and 292.9 respectively. The in vitro intrinsic clearances (Vmax/Km) for ticagrelor glucuronidation by HLM and HIM were 1.42 and 0.36 μL·min-1·mg protein-1, respectively. Study with recombinant human UGTs suggested that multiple UGT isoforms including UGT1A9, UGT1A3, UGT1A4, UGT2B7, UGT1A1, UGT1A7 and UGT1A8 are involved in the conversion of ticagrelor to ticagrelor-O-glucuronide with UGT1A9 showing highest catalytic activity. The results were further supported by the inhibition studies on ticagrelor glucuronidation with typical UGT inhibitors in pooled HLM and HIM. Little or no inhibition of UGT1A1, UGT1A3, UGT1A4, UGT1A6, UGT1A9 and UGT2B7 by ticagrelor and ticagrelor-O-glucuronide was noted. Ticagrelor-O-glucuronide also exhibited limited inhibitory effects toward CYP2C8, CYP2D6 and CYP3A4. In contrast, ticagrelor-O-glucuronide weakly inhibited CYP2B6, CYP2C9 and CYP2C19 activity with apparent IC50 values of 45.0, 20.0 and 18.8 μM, respectively. The potential of ticagrelor-O-glucuronide to cause drug-drug interactions warrant further study.